ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT DELAY (STUDI KASUS PADA PERUSAHAAN SEKTOR TRANSPORTASI PERIODE 2016-2020) - Ratu Ayu Dara Kusuma Arum Surya Putri; Zahwa Amelia Frishella; Laila Hidayatun Najjah; Subadriyah Subadriyah (Jurnal Akuntansi dan Keuangan, 2022)
This study intends to prove the effect between auditor turnover, financial distress and company size on audit delay. This type of research is descriptive research with a quantitative approach. The population used in this research is all transportation sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2016-2020. As for the determination of the sample, researchers use the purposive sampling method where, the sample obtained is based on certain criteria. From the results of research that has been carried out, it was found that the variables that affect audit delay are financial distress variables, while the other two variables, namely auditor turnover and company size, do not affect audit delay.